PERAN GURU DALAM MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN.PAI BERBASIS DARING.PADA MASA PANDEMI.COVID.DI.SMP WAHID.HASYIM MALANG - Mohammad Muhtadi Syah Putra; Rosichin Mansur; Muhammad Fahmi Hidayatullah (VICRATINA, 2022)
Therefore, the teacher's role is needed in motivating students. The teacher's role in studentmotivation is the teacher as a motivator and can be a role model for his students. As rolemodels to motivate students, teachers are required to maintain their behavior and speech.Those who have positive values, besides that, teachers can be respected and respected bystudents. Not because of being a senior teacher but because of his behavior as a teacher whohas authority. The strategy used to motivate student learning is when there are studentswho are less motivated in learning PAI, the teacher communicates with parents andguardians. When communicating, the teacher asks why students are less motivated andwhat difficulties are faced by students when carrying out the learning process at home. Theteacher always gives encouragement and motivation to all students through WhatsApp. Theresults of PAI teachers in increasing student motivation are that students are moreenthusiastic in learning. In this case, because teachers play a role in increasing studentlearning motivation in every online learning, parents and teachers work together tomotivate students